A TICT based NIR-fluorescent probe for human serum albumin: a pre-clinical diagnosis in blood serum - Reja, Shahi Imam; Khan, Imran A.; Bhalla, Vandana; Kumar, Manoj (Chemical communications (Cambridge, England), 2016)
A TICT based NIR-fluorescent probe 3 has been designed and synthesized, which selectively detects HSA with fluorescence enhancement in blood plasma with a detection limit of 11 nM among the various proteins, nucleotides and thiols tested.